1998
DOI: 10.1101/gad.12.13.1941
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the anti-apoptotic PI(3)K/Akt/Bad pathway by stress

Abstract: The initiation of apoptosis often transpires in the presence of agents that regulate cell survival. This study evaluated the effects of stress-induced ceramide on the anti-apoptotic activity of the phosphoinositide-3 kinase [PI(3)K] pathway. PI(3)K activity is directly down-regulated by stress-induced ceramide in a dose-dependent manner with rapid kinetics and high specificity. Ceramide inhibition of PI(3)K is dependent on acid-sphingomyelinase. Down-regulation of PI(3)K by ceramide results in inhibition of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
137
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(148 citation statements)
references
References 37 publications
10
137
0
Order By: Relevance
“…Moreover researchers have used labeled PH domains as a means of measuring 3-phosphoinositide generation in vivo (34,35), suggesting that C 2 -ceramide was probably blocking the activation of PI 3-kinase or the accumulation of PI(3,4)P 2 or PI(3,4,5)P 3 . Although others and we have demonstrated that C 2 -ceramide has no effect on PI 3-kinase in NIH-3T3 fibroblasts or 3T3-L1 adipocytes (9, 10, 13, 15, 22, 36 -39), contradicting reports have suggested that C 2 -ceramide potently inhibits PI 3-kinase activation (11,40,41). To confirm that the effects of C 2 -ceramide did not result from its inhibition of PI 3-kinase we evaluated whether C 2 -ceramide blocked activation of Akt/PKB triggered by directly introducing PI(3,4,5)P 3 into intracellular domains.…”
Section: Ceramide Blocks the Effects Of Insulin On Both The Ph Domainmentioning
confidence: 66%
See 1 more Smart Citation
“…Moreover researchers have used labeled PH domains as a means of measuring 3-phosphoinositide generation in vivo (34,35), suggesting that C 2 -ceramide was probably blocking the activation of PI 3-kinase or the accumulation of PI(3,4)P 2 or PI(3,4,5)P 3 . Although others and we have demonstrated that C 2 -ceramide has no effect on PI 3-kinase in NIH-3T3 fibroblasts or 3T3-L1 adipocytes (9, 10, 13, 15, 22, 36 -39), contradicting reports have suggested that C 2 -ceramide potently inhibits PI 3-kinase activation (11,40,41). To confirm that the effects of C 2 -ceramide did not result from its inhibition of PI 3-kinase we evaluated whether C 2 -ceramide blocked activation of Akt/PKB triggered by directly introducing PI(3,4,5)P 3 into intracellular domains.…”
Section: Ceramide Blocks the Effects Of Insulin On Both The Ph Domainmentioning
confidence: 66%
“…2 In the majority of studies (9, 10, 15, 38 -40), 2 but not all (11,40,41), ceramide analogs were shown to have no effect on hormone-stimulated PI 3-kinase. Moreover others and we have demonstrated previously that ceramide does not inhibit 3Ј-phosphoinositide production by insulin or other hormonal agonists (14,22).…”
Section: Overexpression Of the Sv40 Small T Antigen Prevents The Inhimentioning
confidence: 99%
“…Akt is an important anti-apoptotic protein through which survival signals suppress cell death induced by growth factor withdrawal, cell cycle discordance, and detachment of cells from their extracellular matrix, but its role in influencing cell fate during other conditions of stress has been more controversial. Several studies have reported that environmental stresses capable of inducing apoptosis, such as UVC, ionizing radiation (IR), and hyperosmotic stress lead to the downregulation of the PI3K/Akt pathway (Meier et al, 1998;Zhou et al, 1998;Zundel and Giaccia, 1998), and it has been suggested that such downregulation is important in the apoptotic process. However, Akt is activated in response to oxidant injury as well as several other stresses known to exert their cytotoxic effects in part through generation of ROS or perturbations in cellular redox status (Konishi et al, 1997;Sonoda et al, 1999;Klotz et al, 2000;Wang et al, 2000b;Huang et al, 2001).…”
Section: Pi3-kinase/akt Pathwaymentioning
confidence: 99%
“…Interestingly, activation of PKB can be down-regulated by certain stress stimuli which increase intracellular ceramide [43,44]. Thus agents which activate acidic sphingomyelinase (such as tumour necrosis factor-α) may antagonize PKB activity.…”
Section: Phosphatidylinositol 3-kinase (Pi-3k) Mediates Pkb Activationmentioning
confidence: 99%